Participatory democracy: challenges and disillusions in the xxi century (2010)
This article synthesizes reflections and proposals concerning participatory democracy from a revision of French and Latin American literature. The paradox according to which the implementation of participatory democracy still confronts obstacles in spite of an apparently favorable legitimation context is analyzed. Likewise, it questions some theoretic and empiric postulates regarding the relations among representation, participation and democracy strengthening. That revision allows a critical balance, without falling into an excessive skepticism or an ingenuous idealization of participatory democracy, thus forwarding some research paths.